Da mitologia ancestral à mitologia musical : reflexos do espetacular e do hiperespetacular em videoclipes de David Bowie, Kiss e Lady Gaga - Paludo, Ticiano Ricardo (2017)
This thesis aims to study the articulations and tensions that exist in the 21st century musical myths, and will verify the possibility of tracing a 2000’s mythic construction paradigm to understand the plurality of proposals, platforms and contemporary languages. For this, it presents its own analysis method to think about the total artist concept. An illustrative cut occurs through David Bowie, Kiss and Lady Gaga’s music videos. Bowie will be presented as one of the very first total artists in pop culture, fowward by Kiss, and Gaga. Music videos will be presented as encapsulated operas. In the end, the thesis discuss the adversongs, an union between music, and advertising, apex of the total artist of the 2010 decade.